PENGARUH PENGGUNAAN MODEL PROBLEM BESED LEARNING BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS V SD GKPS SARIBUDOLOK - Sinaga, Dearin Jely; Regina Sipayung; Eka Kartika Silalahi; Patri Janson Silaban; Antonius Remigus Abi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the effect of the Problem-Based Learning (PBL) model assisted by Wordwall media on the mathematics learning outcomes of fifth-grade students at SD GKPS Saribudolok, focusing on the topic of perimeter and area of plane figures. This research employed an experimental method with a One Group Pretest-Posttest Design without a control group. A total of 36 students from class V-A participated as research subjects. Data were collected through pretests, posttests, and student response questionnaires. Data analysis was conducted using the Shapiro-Wilk normality test and one-sample t-test with the assistance of SPSS version 25. The results indicate a significant improvement in students' learning outcomes after the implementation of the PBL model assisted by Wordwall. The average pretest score of 59.33 (categorized as poor) increased to 79.88 (categorized as good) in the posttest, with 75% of students achieving mastery learning above the minimum competency criteria. Normality tests confirmed that the data were normally distributed (p > 0.05), and the t-test results showed that tcount ≥ ttable (3.820 ≥ 2.030) with a significance value of 0.001 < 0.05, indicating a positive and significant effect of using PBL with Wordwall on mathematics learning outcomes. Furthermore, students’ responses toward the learning model were categorized as very good (mean = 92.16). Thus, PBL assisted by Wordwall can be considered an effective learning strategy to improve mathematics learning achievement and student motivation.